Adjuvant therapy following curative treatments for hepatocellular carcinoma: current dilemmas and prospects - Guo, Bin; Chen, Qian; Liu, Zhicheng; Chen, Xiaoping; Zhu, Peng (Frontiers in Oncology, 2023)
Curative surgical treatments, mainly liver resection, are still one of the optimal options for patients with early-, mid-, and even progression-stage hepatocellular carcinoma (HCC). However, the recurrence rate within 5 years after surgery is as high as 70%, especially in patients with high risk factors for recurrence, most of whom experience early recurrence within 2 years. Effective adjuvant therapy may improve prognosis, previous studies found that adjuvant transarterial chemoembolization, antiviral, and traditional Chinese medicine et al. were helpful in preventing HCC recurrence. Nevertheless, due to controversial results or lack of high-level evidence, there is no standardized postoperative management protocol worldwide at present. Continued exploration of effective postoperative adjuvant treatments to improve surgical prognosis is necessary.